S-MADE: Interactive storytelling architecture through goal execution and decomposition - CAI, Yundong (Institutional Knowledge at Singapore Management University, 2007)
Interactive storytelling, emerging with virtual reality technology, has attracted a lot of research interests in recent years. In order to bridge the gap between story generation and story presentation, some hybrid narrative models are raised. In this paper, we propose a new hybrid interactive storytelling architecture S-MADE. It combines the story plot generation and character performance through goal execution and decomposition mechanism. Fuzzy Cognitive Goal Net (FCGN) is a goal modeling tool for modeling the story scenario and character behaviors. The goal decomposition algorithm enables for director agent to dispatch acts to characters easily. With this system, dynamic storylines as well as character behaviors are created in real time simultaneously, which is hard to be achieved in traditional approaches. Audiences are able to experience different perspectives through interactions with director and characters.